Seismicity Pattern Analysis in and around Shillong Great Earthquake of 1897 - Panthi, Ananta; Bhattarai, Jyoti (Himalayan Physics, 2015)
The seismicity data of the last 50 years (1963-2012) of the region bounded by 89° - 93° E and 24° -28° N have been analyzed for understanding the seismic characteristics in and around Shillong great earthquake of 1897. The distribution of earthquakes for this period shows sporadic nature of seismic activity in the region. The study of earthquake frequency, the spatio-temporal patterns of seismicity, the focal depth distribution, and the energy release pattern during the period 1963-2012 considering the events with cut-off magnitude (mb ≥ 4.5) have revealed that the region is seismically active. It is observed that most of the seismicity over the Shillong region is associated with the Main Central Thrust, Main Boundary Thrust and Transverse faults. The earthquake occurrence pattern is non-uniform and mostly shallow and intermediate focus in nature. Further, it has been observed that there exists a non-uniform pattern of seismic energy release. The Himalayan Physics Year 5, Vol. 5, Kartik 2071 (Nov 2014) Page: 36-38